Physiological characteristics of male U.S. soccer development academy players: differences between age groups and player positions - Chandler, A.; Cintineo, H.; Arent, M.; McFadden, B.; Bozzini, B.; Walker, A.; Poyssick, A.; Mackowski, N.; Maldonado, W.; Arent, S. (The Journal of Strength and Conditioning Research, 2021)
Elite youth soccer players differ both physically and physiologically from their non-elite counterparts, but data in elite youth athletes are limited. Assessing characteristics by both chronological age and by player position may provide information regarding normative athlete characteristics that relate to sport performance. Purpose: To assess physiological characteristics of elite youth male soccer players and evaluate differences between age groups and on-field player positions. Methods: Elite youth male soccer players (N = 86) completed a single testing session to assess physiological characteristics. Percent body fat (BF) and fat-free mass (FFM) were determined using air-displacement plethysmography and athlete-specific density equations. Countermovement jump (CMJ) height was measured and used to calculate absolute (W) and relative (W/kg) anaerobic power. Aerobic capacity (VO2max) was determined by indirect calorimetry during a maximal graded exercise test. Differences between age groups (U15: n = 39 Mage = 14.3 ± 1.0 years; U18: n = 47; Mage = 16.8 ± 0.8 years) were assessed using independent t-tests and differences by on-field positions (forward [FW], defender [DF], midfielder [MD], goalkeeper [GK]) were analyzed using one-way ANOVA with Tukey HSD pairwise comparisons (a = 0.05). Results: U18 were taller (+7.2 cm), heavier (+13.0 kg), and had more FFM (+12.6 kg), yet lower VO2max (-2.8 ml/kg/min) than U15 (p < 0.01). CMJ was higher in U18 (+4.2 cm; p = 0.02) and relative power was greater in U15 (+8.3 W; p = 0.03), but there were no differences in absolute power output. Player characteristics (mean ± SD) by position are displayed in Table 1. GK were taller than MD (p = 0.002), heavier than MD (p < 0.001) and DF (p = 0.03), and had higher BF than FW (p = 0.01). MD were shorter than FW (p = 0.02) and DF (p = 0.04), weighed less than FW (p = 0.01), and had lower FFM compared to both FW (p = 0.003) and GK (p = 0.004). While Vo2max did not differ by position, CMJ was higher in FW compared to MD (p = 0.04). Both GK and FW produced more absolute power than DF and MD (p < 0.05), but there were no differences in relative power by position. Conclusions: Anthropometrics and CMJ varied by both age and position, but VO2max only differed by age. The higher FFM and total bodyweight in the older athletes may contribute to their higher CMJ yet lower relative power and Vo2max. Higher absolute power production among GK and FW, along with the physical differences between positions, is likely reflective of varying positional demands. Practical Application: Anthropometric characteristics may be determinants of on-field success among elite male youth soccer athletes. The impacts of age, physical maturation, and development on performance suggest it is beneficial for athletes to compete within their age cohort rather than advance prematurely, as a smaller body size may place younger athletes at a disadvantage.